Chemopreventive effect of galangin against benzo(a)pyrene-induced stomach tumorigenesis through modulating aryl hydrocarbon receptor in Swiss albino mice. (September 2021) - Wang, L; Xue, J; Wei, F; Zheng, G; Cheng, M; Liu, S
The present study was aimed to evaluate the chemopreventive potential of galangin against benzo(a)pyrene (BaP)-induced stomach carcinogenesis in Swiss albino mice. Stomach cancer was induced in experimental mice using BaP oral administration. The mice were treated with galangin (10 mg/kg b.wt.) before and during BaP administration. Oral administration of galangin at a dose of 10 mg/kg b.wt. significantly (p < 0.05) prevented the tumor incidence, tumor volume in the experimental animals. Further, galangin pretreatment prevents BaP-induced lipid peroxidation and restores BaP-mediated loss of cellular antioxidants status. It has also been found that galangin prevents BaP-induced activation of phase I detoxification enzymes. Furthermore, galangin pretreatment prevented the BaP-induced overexpression of cytochrome P450s isoform genes (CYP1A1, CYP1B1), aryl hydrocarbon receptor system (AhR, ARNT), transcriptional activators (CBP/p300, NF-kB), tumor growth factors, proto-oncogenes, invasion markers (TGFB, SRC-1, MYC, iNOS, MMP2, MMP9) and Phase II metabolic isoenzyme genes (GST) in the stomach tissue homogenate when compared to the control groups. The western blot results confirm that galangin (10 mg/kg. b.wt.) treatment significantly prevented the BaP-mediated expression of ArR, ARNT, and CYP1A1 proteins in the mouse stomach tissue. Therefore, the present results confirm that galangin prevents BaP-induced stomach carcinogenesis probably through modulating ArR and ARNT expression in the experimental mice.